Fostering Learning Discipline: Exploring Token Economy Implementation at Student - Dicky Ardhana, Achmad; Setiawan Wicaksono, Awang (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Education plays a crucial role in shaping human life and is deeply embedded in the structure of families, communities, and nations as a whole. This critical stage serves as a foundation for lifelong learning, where students acquire essential skills such as reading, writing, and arithmetic. The aim of this research is to enhance the learning discipline of students at SD Muhammadiyah Manyar Gresik by implementing the token economy technique. The research method used is an experiment involving pre-tests and post-tests, with the subjects consisting of participating fourth-grade students. The study begins with observations and initial interviews to gather information regarding students' learning discipline behaviors and the teachers' understanding of the issues present in the classroom. The research results indicate that the implementation of the Token Economy model at SD Muhammadiyah Manyar Gresik significantly improves students' learning discipline, as evidenced by increased active participation in class, timely task submissions, and awareness of cleanliness. The implications of this research highlight the importance of reward-based interventions in enhancing learning discipline, where the adoption of the Token Economy model can serve as an innovative strategy to address disciplinary issues in schools, potentially improving overall educational outcomes.